Strategi Penerapan Pedoman Gizi Seimbang dalam Membangun Generasi Emas yang Cerdas dan Sehat di SD Negeri Penambangan - Ciplis Gema Qori’ah; Adhitya Wardhono; Bhim Prakoso; M Abd Nasir; Agung Nugroho Puspito; Nabila Nuraini Eka Putri; Dian Aulia Ramadhani; Loveis Critzylla Firdaus; Anggi Najwa Puteri; Hurin Silmi Maulida; Maulidya Nur Apriliantika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Education is very important in human life, because every individual has the right to get it in order to develop. Education is seen as a process that allows a person to grow and develop their potential. According to Ki Hajar Dewantara, education aims to advance the development of the child's character, mind and body. Education has a big role in producing quality human resources and being able to compete healthily. Elementary school (SD) is an educational institution that teaches the basics of intelligence, knowledge, personality, noble character, and life skills to develop potential and prepare students to continue their education to a higher level. In this context, SD Negeri Penambangan in Curahdami sub-district, Bondowoso district was chosen to implement a social project for the Pancasila Education course. The school has limited access, a less strategic location, and a small number of students, 47 students with an average class size of less than 10. Some students also do not understand basic reading, writing and arithmetic. In addition, many of them do not eat breakfast before going to school and buy unhealthy snacks, such as fried foods and packaged drinks, during break time. The project was carried out in four stages: planning, survey, implementation and closure, with the aim of providing students with an understanding of the importance of a healthy diet and balanced nutrition. The material delivery that we use such as direct material exposure, Video playback of material, reading and writing, practice doing hand washing activities, and building puzzles. At the end of the activity, it is expected that students not only understand the theory of balanced nutrition, but also can apply it in everyday life, both at home and at school. Teachers and parents are expected to support students in choosing healthy food, and schools can create a culture of healthy living that supports students' health and learning achievement. Thus, students are expected to grow into healthy, smart, and productive individuals.